Preventive measures against COVID-19 in the development of dental practice - Davila Auqui, Jacqueline Doris (2021)
COVID-19 in Dentistry is a public health priority for which a series of drastic preventive measures have been applied to help prevent community contagion of the virus, the objective of this study is to describe preventive measures against Covid-19 in the development of dental practice. That is why the importance of the use of all protection barriers such as the use of personal protective equipment (PPE) for dentists, hand washing, screening, triage of patients, cleaning and disinfection of surfaces, preparation of the clinical field, protocol prior to care, provisions for the management of stomatological procedures, use of antiseptic rinses prior to the procedure, placement of a rubber dam, use of high-powered evacuation suctors, disinfection at the end of treatment and dental waste management. It is concluded that it is necessary to use preventive biosafety measures through the correct execution of standards such as hand washing protocol, the use of a disinfectant such as 70% alcohol and the use of a filtering respirator such as N95; in addition to the use of an antiseptic rinse prior to the procedure, the placement of a rubber dam, and the use of a high-powered evacuation suction device.